Chapter 8 Not seeing Auschwitz Memory, generation and representations of the Holocaust in twenty-first century French comics - Gorrara, Claire (Taylor & Francis, 2018)
We are reaching a point in history when the generation who experienced the Holocaust as survivors, witnesses or exiles will soon disappear. What happens to our relationship to such a momentous event in global history when our living connection with such a past is broken? To answer this question, this article will explore recent French representations of the Holocaust through the comic book. It will approach such representations from the perspective of the grandchildren of those who were affected by the Holocaust, perhaps the last generation to have personal ties to this wartime past. It will focus specifically on Jérémie Dres's Nous n'irons pas voir Auschwitz (2011), translated as We Won't Go and See Auschwitz. As a "third generation" narrative, Dres's work is attentive to stories of Jewish exile and loss to be found on the margins of Holocaust histories. This perspective translates into an openness towards transnational histories of the Holocaust; a recognition of place as a substitute for living memory and an awareness of comics' potential to innovate in the transmission of Holocaust memories. Ultimately, this article will argue that the contemporary comic book acts as a privileged vehicle of remembrance, indicative of the reordering of Holocaust representations in an age of cultural memory.